Al-Ḥuzn fī Qaṣīdah Riṡā’ al-Andalus li Abī al-Baqā’ al-Randī: Dirāsah Naqdīyah Balāgīyah - Zulhelmi, Zulhelmi; Hafis, Ade; Syarifuddin, Syarifuddin; Ibrahim, Malik (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2023)
حاول هذا البحث إلى تحليل قصيدة